2021
DOI: 10.1002/anie.202104352
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Enantioselective Aldol Reactions Catalyzed by Chiral Nickel(II) Complexes

Abstract: A direct and asymmetric aldol reaction of N-acyl thiazinanethiones with aromatic aldehydes catalyzed by chiral nickel(II) complexes is reported. The reaction gives the corresponding O-TIPS-protected anti-aldol adducts in high yields and with remarkable stereocontrol and atom economy. Furthermore, the straightforward removal of the achiral scaffold provides enantiomerically pure intermediates of synthetic interest, which involve precursors for anti-a-aminob-hydroxy and a,b-dihydroxy carboxylic derivatives. Theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…We just hypothesize that it might be the result of the combination of several geometric and electronic contributions. Although no significant changes in molecular geometries are appreciated, it is important to note that the C•••C distances for the propanoyl-derivative are similar to a previous studied system, [16] but such distances are shortened in the N-azidoacetyl enolate by about 0.10 Å in all transition states, which indicates that it is a late transition state.…”
Section: Theoretical Studiessupporting
confidence: 55%
See 3 more Smart Citations
“…We just hypothesize that it might be the result of the combination of several geometric and electronic contributions. Although no significant changes in molecular geometries are appreciated, it is important to note that the C•••C distances for the propanoyl-derivative are similar to a previous studied system, [16] but such distances are shortened in the N-azidoacetyl enolate by about 0.10 Å in all transition states, which indicates that it is a late transition state.…”
Section: Theoretical Studiessupporting
confidence: 55%
“…[19,20] Particularly, it was found that the N-azidoacetyl-1,3thiazolidine-2-thione (1 in Table 1) reacts with 1.1 equivalents of 4-methoxybenzaldehyde (a) in the presence of 2 mol% of [(S)-Tol-BINAP]NiCl 2 , TIPSOTf (1.5 equivalents), and lutidine (1.5 equivalents) to give anti aldol adduct 1 a in a 95 % yield with outstanding stereocontrol (dr > 95 : 5, ee 99 %). [16] Despite such an excellent result, we decided to examine in detail the influence of the endocyclic heteroatom as well as the size of the heterocycle. Thus, we tested parallel reactions with Nazidoacetyl-1,3-oxazolidine-2-thione (2 in Table 1) containing a five-membered oxygenated scaffold and the related six-membered counterparts (3-4 in Table 1).…”
Section: Optimization Of the Reaction Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the azido thiazolidinethione 16 (R = N 3 ) proved especially successful and afforded in just 2 h the a-azido-b-silyloxy adduct 27 a virtually as a single stereoisomer (dr 95:5, 99 % ee) in a yield of 93 %. [13] The configuration of 5 a was established as the (2S,3R)anti-adduct through X-ray analysis of the benzyl amide derivative 28, [14] which was easily prepared by nucleophilic displacement of the scaffold of 5 a with (S)-1-phenyl-1ethylamine (Scheme 3). [15] Furthermore, amides 29 and 30 were isolated in up to 99 % yield after reaction with morpholine and N-methoxy-N-methylamine, respectively.…”
Section: Angewandte Chemiementioning
confidence: 99%